A STUDY ON STRATEGIES FOR TEACHING SPEAKING AND READING COMPREHENSION SKILLS - ., AHMAD; ., Prof. Dr.I Ketut Seken,MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Universitas Pendidikan Ganesha, 2013)
The central intention of this study was to analyze the English teachersâ?? strategies in teaching speaking and reading comprehension skills in SMPN 1 Selong. It was conducted to get detailed information about the studentsâ?? responses toward their teachersâ?? strategies in teaching speaking and reading comprehension skills. This study employed a qualitative research design. Necessary data were gathered using open-ended question, classroom observation, interview, and questionnaire. The result of this study revealed that the three teachers applied teaching speaking and reading comprehension skills strategies in three stages; Pre-stages, Whilst-stages and Post-Stages. From the three teachers observed, they employed various stategies in each stage with different reasons. In general the studentsâ?? responses toward their teachersâ?? strategies in teaching speaking and reading comprehensions skills were good enough as their instructions were clear and understandable. Based on those finding, it can be concluded that the English teachers need to increase their knowledge and experience in order to understand the concept and reasons in using the strategies for teaching speaking and reading comprehension. This study recommended that English teachers should have awareness to the significance in choosing the appropriate strategies for teaching speaking and reading comprehension skills. So that the learning process can run effectively.keyword : Strategy, Speaking, Reading